Liming remediates soil acidity and improves crop yield and profitability - a meta-analysis - Enesi, Rebecca Oiza; Dyck, Miles; Chang, Scott; Thilakarathna, Malinda S.; Fan, Xiaoli; Strelkov, Stephen; Gorim, Linda Yuya (Frontiers in Agronomy, 2023)
Soil acidity reduces base cations required for plant growth and may result in phytotoxic concentrations of soluble aluminum. Liming acidic soils is generally promoted as an effective management practice to increase soil pH, base cation concentrations and ameliorate toxicity caused by aluminum and manganese. Through a global literature review using data published from field experiments on liming, the objective of this paper is to understand the effects of liming on soil pH, crop yields, and economic profitability. The results show that liming positively influenced crop yields and soil pH, implying that various lime sources can increase soil pH and crop productivity. The effect sizes of liming on crop yields when lime was incorporated into soils were higher than surface application irrespective of tillage practice. Liming under no-tillage (NT) compared to conventional tillage (CT) management showed higher effect sizes for crop yields. Liming increased effect sizes for crop yields in fertilized compared with unfertilized trials. CaSO4, Ca(OH)2 and CaCO3 showed higher effect sizes when compared with Cement Klin Dust (CKD), MgCO3 and wood ash. The results show that liming increased yields for all crops except potatoes and oats. Liming generally increases soil pH. Changes in soil pH increased with higher lime application rates and yield increases were proportional to the magnitude of increases in soil pH. The profitability of liming differed with crop type and liming rate, being more profitable at lower liming rates. Overall, this meta-analysis shows that liming decreases soil acidity and improves crop yields. Attaining maximum gains from liming agricultural crops under acidic soil conditions requires an understanding of the appropriate lime rates required for specific crops and soil types to ensure overall profitability for producers and sustainable improvement of soil health.